Analgesic efficacy and safety of morphine in the Procedural Pain in Premature Infants (Poppi) study: randomised placebo-controlled trial - Hartley, C; Moultrie, FA; Hoskin, A; Green, G; Monk, V; Bell, JL; King, AR; Buckle, M; Van Der Vaart, ML; Gursul, D; Goksan, S; Juszczak, ER; et al. (Elsevier, 2018)
Background Infant pain has immediate and long-term consequences, but is undertreated due to a lack of evidence-based analgesics. Although morphine is frequently used to sedate ventilated infants, its analgesic efficacy is unclear. We aimed to establish whether oral morphine could provide effective and safe analgesia in non-ventilated premature infants for acute procedural pain. Methods In this single-centre masked trial, 31 infants at the John Radcliffe Hospital, UK were randomised to receive 100μg/kg of oral morphine sulphate or placebo 1 hour before a clinically-required heel lance and retinopathy of prematurity (ROP) screening examination, on the same occasion. Eligible infants were born prematurely at <32 weeks’ gestation or with a birth weight of <1501g, and had a gestational age of 34─42 weeks at time of study. The co-primary outcomes were the Premature Infant Pain Profile-Revised (PIPP-R) score after ROP screening and the magnitude of noxious-evoked brain activity following heel lancing. Secondary outcomes assessed physiological stability and safety. The study was registered (European Clinical Trials Database:2014-003237-25). Findings Between 30 October 2016 and 17 November 2017, 15 infants were randomised to receive morphine and 16 placebo (1 withdrew). The predefined stopping boundary was crossed, and trial recruitment stopped due to profound respiratory adverse effects of morphine without suggestion of analgesic efficacy. Neither primary outcome measure was significantly different between the groups (PIPP-R following ROP screening: morphine: PIPP-R mean±SD =11.1±3.2; placebo: PIPP-R=10.5±3.4; mean difference 0.5, 95% CI:-2.0─3.0, p=0.66; noxious-evoked brain activity following heel lancing: morphine: median (IQR) 0.99 (0.40─1.56); placebo: 0.75 (0.33─1.22); median difference 0.25, 95% CI:-0.16─0.80, p=0.25). Interpretation Administration of oral morphine (100μg/kg) to non-ventilated premature infants has the potential for harm without analgesic efficacy. We do not recommend oral morphine for ROP screening and strongly advise caution if considering its use for other acute painful procedures in non-ventilated premature infants.